Wireless telecommunications systems and networks - Mullett, Gary J. (Thomson Delmar Learning, 2006)
Provides a comprehensive coverage of the fundamental aspects of several forms of wireless telecommunications systems used to extend the reach of the wired public or private data network. This text is written primarily for either the two- or four-year college level student who is studying the technical aspects of wireless systems and networks.